Prevalence and factors associated with underweight among children under five born to adolescent mothers: Evidence from the 2022 Kenya Demographic and Health Survey - Alfred Omutoj; Henry Prosper Dade; Annitah Kagali; Samuel Salu; David Mensah Otoo; Betty Oloo; Prince Tsekpetse (PLoS ONE, 2026)
Background Undernutrition remains a major public health concern in low- and middle-income countries, with children born to adolescent mothers being particularly at risk of underweight. In Kenya, despite high adolescent birth rates, there is limited nationally representative evidence on the prevalence of underweight and its determinants among children under five years born to adolescent mothers. This study examined the prevalence and factors associated with underweight among Kenyan children under five years of age born to adolescent mothers, using nationally representative data from the 2022 Kenya Demographic and Health Survey (KDHS). Methods This study was a cross-sectional analysis of data from the child recode file (KR) of the 2022 KDHS, comprising a weighted sample of 819 children under five years born to adolescent mothers aged 15–19 years. Underweight was defined as a weight-for-age Z-score of less than −2 SD. Modified Poisson regression analyses were performed to identify factors associated with underweight. All analyses accounted for the complex survey design and sampling weights. Results from the bivariate model are presented as crude prevalence ratios (CPR), while results from the multivariable model were presented as adjusted prevalence ratios (APR). Statistical significance was set at P < 0.05. Results The prevalence of underweight among Kenyan children born to adolescent mothers was 11.03% (n = 77/702; 95% CI: 8.65–13.97). In the multivariable model, children of married adolescent mothers were more likely to be underweight (APR = 2.22; 95% CI: 1.15–4.28; P = 0.018) than those of unmarried mothers. Additionally, the prevalence of underweight increased with an increase in the child’s age. Children aged 6–23 months (APR = 2.73; 95% CI: 1.22–6.12; P = 0.015) and those aged ≥24 months (APR = 4.35; 95% CI: 1.84–10.30; P = 0.001) were more likely to be underweight than those aged six months and below. Conclusion Approximately 1 in 9 children under five years born to adolescent mothers in Kenya were underweight. Being in a marital union and an increase in the child’s age emerged as key factors associated with underweight among children born to adolescent mothers. These findings highlight the need for targeted interventions to prevent early marriage among adolescent girls and to improvee complementary feeding practices among adolescent mothers to reduce the risk of underweight among their children..